Redefining the Terms of National Belonging in War and Peace, in Randolph Bourne’s Critique of the Great War - Canelo, Maria José (2019)
This paper looks into Randolph Bourne’s cultural critique at the time of the United States entry into World War I. As one of the few intellectuals who opposed the war, Bourne brought into light the interdependence between war and the State: “War is the health of the State” is his phrase and has resonated ever since. He looked well beyond nationalist hysteria and economic imperialism to examine the reasons for the State to support militarism, but he also sought concrete pacifist alternatives to the U.S. intervention in the war that involved the intellectuals in particular. This paper sheds light on these alternatives based on Bourne’s anti-war writings, namely his proposals for an educational service to prepare the nation for creative rather than destructive action, and the intellectuals’ renewal of the dialogue between democracy and pacifism en route to a transnational understanding of community and belonging.